A Systematic Review of the Cost-effectiveness of Perampanel in the Treatment of Epilepsy - Doan Duy Linh, Nguyen; Huy Tuan Kiet, Pham; Thi Hon, Dang; Tien Dat, Tran; Xuan Bach, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2DO - 10.25073/2588-1132/vnumps.4377, 2022)
Objective: Epilepsy is a chronic non-communicable disease that can affect all ages, genders, races, and social classes with large treatment costs that vary widely between countries and regions. Perampanel is a new generation of antiepileptic drugs (AEDs), but cost-effectiveness reports are inconsistent in several countries that have conducted pharmacoeconomic evaluations. Study with the objective of systematically summarizing the evidence on the cost-effectiveness of Perampanel for the treatment of epilepsy. Methods: An exhaustive search was performed in four publication databases. Evaluation of the reporting quality of the studies using the CHEERS checklist. Results: Findings: Costs were lower in the Perampanel group than in the Lacosamide group (Perampanel 8mg/day vs. Lacosamide 400mg/day - Total cost: $2390 (12.89%), but higher than in the antiepilepsy drugs group without perampanel (Total Direct Cost: 5475 Euro and Total Indirect Cost: -5288 Euro, Total Cost: 188 Euro) and the group with recent add-on regime such as Brivaracetam (3188 Euro in total). When compared with the Lacosamide group, the Perampanel group showed increased outcomes in all three outcomes (convulsions, LY, and QALY). Similarly, the Perampanel group showed increased outcomes in all three outcomes (convulsions, LY, and QALY) compared with groups without Perampanel. Meanwhile, QALY in the Perampanel group was lower than in the Brivaracetam group (total of 0.059 QALY). Conclusions: Perampanel as an adjunct therapy for antiepilepsy drugs may be a cost-effective treatment option in the management of epilepsy. Keywords: Fycompa, perampanel, seizure, epilepsy, systematic review, cost-effective. References [1] R. S. Fisher, C. Acevedo, A. Arzimanoglou, A. Bogacz, J. H. Cross, C. E. Elger et al., ILAE Official Report: a Practical Clinical Definition of Epilepsy. Epilepsia, Vol. 55, No. 4, 2014, pp. 475-482. [2] K. M. Fiest, K. M. Sauro, S. Wiebe, S. B. Patten, C. S. Kwon, J. Dykeman, et al., Prevalence and Incidence of Epilepsy: A Systematic Review and Meta-analysis of International Studies, Neurology, Vol. 88, No. 3, 2017, pp. 296-303. [3] A. C. Meyer, T. Dua, J. Ma, S. Saxena, G. Birbeck, Global Disparities in The epilepsy Treatment Gap: a Systematic Review, Bull World Health Organ, Vol. 88, No. 4, 2010, pp. 260-266. [4] GBD, Neurology Collaborators, Global, Regional, and National Burden of Neurological Disorders, 1990-2016: a Systematic Analysis for the Global Burden of Disease Study 2016, Lancet Neurol, Vol. 18, No. 5, 2019, pp. 459-480. [5] S. Y. Chen, N. Wu, L. Boulanger, P. Sacco, Antiepileptic Drug Treatment Patterns and Economic Burden of Commercially-insured Patients with Refractory Epilepsy with Partial Onset Seizures in the United States, J Med Econ, Vol. 16, No. 2, 2013, pp. 240-248. [6] J. A. Cramer, Z. J. Wang, E. Chang, A. Powers, R. Copher, D. Cherepanov et al., Healthcare Utilization and Costs in Adults with Stable and Uncontrolled Epilepsy, Epilepsy Behav, Vol. 31, 2014, pp. 356-362. [7] K. Allers, B. M. Essue, M. L. Hackett, J. Muhunthan, C. S. Anderson, K. Pickles et al., The Economic Impact of Epilepsy: a Systematic Review, BMC Neurol, Vol. 15, 2015, pp. 245. [8] D. L. Thuy, Evaluation of the Use of Antiepileptic Drugs in the Community in Thai Nguyen Province [Master Thesis], Hanoi, Vietnam, Hanoi University of Pharmacy, 2010 (in Vietnamese). [9] N. C. Hoan, H. D. Muoi, Clinical Features of Major Generalized Epilepsy in Pediatric Patients Aged 5 to 15 Years. Journal of Practical Medicine, Vol. 860, No. 3, 2013, pp. 48-50 (in Vietnamese). [10] Nation Institute for Health and Clinical Excellence, The Epilepsies: The Diagnosis and Management of the Epilepsies in Adults and Children in Primary and Secondary Care: Pharmacological Update of Clinical Guideline 20, London, 2012. [11] Asia WHOROfS-E, Epilepsy: a Manual for Physicians, 2004. [12] G. Tremblay, D. Howard, W. Tsong, V. Patel, J. D. Rosendo, Cost-effectiveness of Perampanel for The Treatment of Primary Generalized Tonic-Clonic Seizures (PGTCS) in Epilepsy: A Spanish Perspective, Epilepsy & Behavior: E&B, Vol. 86, 2018; pp. 108-115. [13] D. Husereau, M. Drummond, S. Petrou, C. Carswell, D. Moher, D. Greenberg et al., Consolidated Health Economic Evaluation Reporting Standards (CHEERS) Statement, Bmj, Vol. 346, 2013, pp. f1049. [14] D. Zhang, X. Li, J. Ding, X. Ke, W. Ding, Y. Ren, et al., Value of Perampanel as Adjunctive Treatment for Partial-Onset Seizures in Epilepsy: Cost-Effectiveness and Budget Impact Analysis, Vol. 9, 2021, pp. 866. [15] S. Väätäinen, E. Soini, J. Peltola, M. Charokopou, M. Taiha, R. Kälviäinen, Economic Value of Adjunctive Brivaracetam Treatment Strategy for Focal Onset Seizures in Finland, Advances in Therapy, Vol. 37, No. 1, 2020, pp. 477-500. [16] H. M. Hamer, A. Spottke, C. Aletsee, S. Knake, J. Reis, A. Strzelczyk et al., Direct and Indirect Costs of Refractory Epilepsy in a Tertiary Epilepsy Center in Germany, Epilepsia, Vol 47, No. 12, 2006, pp. 2165-2172. [17] L. Gao, L. Xia, S. Q. Pan, T. Xiong, S. C. Li, Burden of Epilepsy: a Prevalence-based Cost of Illness Study of Direct, Indirect and Intangible Costs for Epilepsy, Epilepsy Research, Vol. 110, 2015, pp. 146-156. [18] M. Hiligsmann, C. Cooper, F. Guillemin, M. C. Hochberg, P. Tugwell, N. Arden et al., A reference Case for Economic Evaluations in Osteoarthritis: an Expert Consensus Article from the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO), Paper Presented at Seminars in Arthritis and Rheumatism, 2014. [19] M. Hiligsmann, C. Cooper, N. Arden, M. Boers, J. C. Branco, M. L. Brandi et al., Health Economics in the Field of Osteoarthritis: an Expert's Consensus Paper From the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO), Paper Presented at Seminars in Arthritis and Rheumatism, 2013. [20] K. Bolin, L. Forsgren, The Cost-Effectiveness of Newer Epilepsy Treatments: a Review of The Literature on Partial-onset Seizures, Pharmaco Economic, Vol. 30, No. 10, 2012, pp. 903-923.